Optimizing the Potential of Nila Fish as a Mulur Village’s Flagship Product through Assistance in Developing Presto Nila for the Women’s Group (PKK) of Mulur Village - Made Wedaswari; Windy Rizkaprilisa; Ahmad Dzakiyuddin (Dimas: Jurnal Pemikiran Agama untuk Pemberdayaan, 2025)
This community service program was conducted in Mulur Village to utilize its freshwater potential by developing Presto Nila Mulur, a high-value processed fish product. The program targeted the women’s group (PKK) affected by mass layoffs at PT Sritex, aiming to enhance their entrepreneurial capacity. The Participatory Learning and Action (PLA) method was employed to enhance participants' knowledge, technical skills, and business management capabilities through socialization, hands-on training, mentoring, and evaluation. Activities covered fish processing, vacuum packaging, and food safety practices. Quantitative evaluations showed significant progress, with knowledge increasing from 39% to 96%, skills rising from 60% to 94%, and motivation increasing from 40% to 95%. These results confirm the program’s effectiveness in developing both technical competence and entrepreneurial motivation, leading to the successful commercialization of Presto Nila Mulur as a ready to eat local specialty. Future initiatives should focus on expanding market access through digital platforms, retail collaborations, and culinary tourism development.